Pengaruh Kualitas Pelayanan, Lokasi, dan Produk Pembiayaan terhadap Pengembangan UMKM Nasabah (Studi Bank Wakaf Mikro Pesantren Mawaridusallam) - Putri Aulia; Pani Akhiruddin Siregar (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Background: Indonesia as a country with the largest Muslim population in the world has a very large potential for cash waqf, but this has not been optimally developed. Purpose: This study aims to determine the effect of service quality, location, and financing products on the development of MSME customers. Methods: Quantitative research design with Cross Sectional study design. The research was conducted in June 2023. The population in this study were 86 customers. The sample in the study were 71 customers obtained using the slovin formula. Data analysis used the Kolmogorov-Smirnov test, multiple linear regression, Test F and Test R2. Result: the test results show that the value of Fcount (23.520) > Ftable (2.74) with a value of Sig F = 0.00 <0.05 means that the variables of Quality of Service, Location and Financing Product simultaneously (together) have a significant effect on the MSME Development variable. Conclusion: Service Quality, Location, and financing products have a significant impact on MSME development.